(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article "Innovative Educational Technologies in Language and Literature Teaching: Opening New Horizons of Learning" presents an overview of modern technological approaches to language and literature teaching. The article discusses various innovative methods such as the use of online platforms and applications, virtual and augmented reality, as well as social media and learning communities. The advantages and challenges of using these technologies in the educational process are analyzed and examples of their successful application are presented. In addition, the article provides perspectives on the development of innovative teaching methods and their potential implications for the future of education. The overall impact of innovative technologies on language and literature teaching is evaluated in the context of developing communication skills, critical thinking and understanding of cultural context.